The Soane Museum - Soane, John
Within the principle of rooms, the same control of space was augmented by the use of mirrors and the placing of furniture, so that the solid nature of the fireplace wall was maintained. English architecture at last began to honor the intentions of the Baroque, with a hint of the Victorian yet to come. Yet its elements, with one or two exceptions, are the severe English adaptations of the Renaissance.